Study on 1, 2, 3-Triazole-Containing Quinolines: Promising Pharmacological Hybrid Agents - Leonor Y. Vargas-Méndez; Vladimir V. Kouznetsov (Current Topics on Chemistry and Biochemistry Vol. 3, 2022)
Quinoline and 1,2,3-triazoles have received a lot of interest recently because of their biological significance. Building a single molecular framework containing quinoline and triazole rings, so-called 1,2,3-triazole-based quinolines through molecular hybridization strategy offers a suitable route to new pharmaceutical agents with potent biological proprieties. The chemistry and biology of several 1,2,3-triazole-containing quinoline hybrids are discussed in this chapter, with the goal of better understanding the physicochemical features of triazole-quinoline hybrids to develop novel bioactive chemical entities. As a result, the main Lipinski parameters, as well as an in-silico analysis, are briefly discussed and applied to a few 1,2,3-triazole-quinoline hybrids. This chapter is divided into two sections: the synthetic elements of the hybrids’ manufacture utilizing Cu-catalyzed azide-alkyne cycloaddition technology, and their pharmacological aspects, with a focus on common harmful diseases like malaria, cancer, and human fungal infections.